A Soul Dancing or Plunging: body and presence in literary experiences - Diniz (Universidade de Brasília ‒ UnB, Brasília/DF, Brazil), Ligia G. (Revista Brasileira de Estudos da Presença, 2022)
This paper reflects upon the affective dimension of the experience of reading fiction and poetry. I argue that the space of the imagination allows the approach of literary texts by means of sensations and emotions. Therefore, I formulate a concept of presence suitable for thinking about literary experiences, in which the reader’s body is mobilized by effects triggered by the text when in contact with his imagery.